EPIZOOTIC BOTULISM OF CATTLE IN BRAZIL - Dobereiner, J.; Tokarnia, C. H.; Langenegger, J.; Dutra, I. S. (M H Schaper Gmbh Co Kg, 1992)
The first diagnosis of botulism in cattle in Brazil and it's epizootiology are reviewed. The high prevalence of the disease raised on phosphorus deficient pastures in Savanna regions has caused severe economic losses in the past.The temperature induced microcomplement fixation test (TIMCF) confirmed the clinical-pathological diagnosis in all of the 24 cases studied by this method.The most important reason why botulism has not been controlled satisfactorily in Brazil is the lack of an available effective vaccine (type C and D). Additional prophylactic measures are phosphorus supplementation and removal of carcasses from the pasture.